2007
DOI: 10.1161/circulationaha.107.696583
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Conduction and Morphology in the Atrioventricular Node of Mice With Atrioventricular Canal–Targeted Deletion of Alk3/Bmpr1a Receptor

Abstract: Background-The atrioventricular (AV) node is essential for the sequential excitation and optimized contraction of the adult multichambered heart; however, relatively little is known about its formation from the embryonic AV canal. A recent study demonstrated that signaling by Alk3, the type 1a receptor for bone morphogenetic proteins, in the myocardium of the AV canal was required for the development of both the AV valves and annulus fibrosus. To test the hypothesis that bone morphogenetic protein signaling al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 37 publications
1
43
0
Order By: Relevance
“…Bone morphogenetic protein 2 (Bmp2) is expressed specifically in the embryonic AVC and is required for AVC development, acting to control the AVC-restricted expression of Tbx2 and Tbx3 (Ma et al, 2005;Singh et al, 2012). Accordingly, AVC-restricted deficiency of the Bmp receptor Alk3 (Bmpr1a) results in defective AVN morphogenesis (Gaussin et al, 2005;Stroud et al, 2007). Bmp2/Smad signalling activates Tbx2 to drive its expression in the AVC (Ma et al, 2005;Singh et al, 2009); Tbx20, which is required for heart tube formation and chamber development, represses this activation to confine the expression of Tbx2 to the AVC and delimit the AVC boundary (Singh et al, 2009).…”
Section: Transcriptional Regulation Of Avc and Avn Developmentmentioning
confidence: 99%
“…Bone morphogenetic protein 2 (Bmp2) is expressed specifically in the embryonic AVC and is required for AVC development, acting to control the AVC-restricted expression of Tbx2 and Tbx3 (Ma et al, 2005;Singh et al, 2012). Accordingly, AVC-restricted deficiency of the Bmp receptor Alk3 (Bmpr1a) results in defective AVN morphogenesis (Gaussin et al, 2005;Stroud et al, 2007). Bmp2/Smad signalling activates Tbx2 to drive its expression in the AVC (Ma et al, 2005;Singh et al, 2009); Tbx20, which is required for heart tube formation and chamber development, represses this activation to confine the expression of Tbx2 to the AVC and delimit the AVC boundary (Singh et al, 2009).…”
Section: Transcriptional Regulation Of Avc and Avn Developmentmentioning
confidence: 99%
“…In addition to Cx30.2 expression, recent studies have implicated BMP signaling in mice (Gaussin et al, 2005;Stroud et al, 2007) and Neuregulin and Notch signaling in zebrafish (Milan et al, 2006) in establishing normal AV delay, although the downstream targets of these pathways have not been characterized. Here we have focused on Cx30.2, a crucial gene involved in establishing normal AV delay, and worked upstream to identify Gata4 as a potential nodal point for regulating other genes dedicated to slow AV impulse propagation.…”
Section: The Cx302 Minimal Enhancer Marks a Subset Of Developing Avnmentioning
confidence: 99%
“…In particular, Tbx3, which has been implicated in the human ulnarmammary syndrome, is required for pacemaker development and AVCS specification (Hoogaars et al, 2007;Bakker et al, 2008). More recently, conditional deletion of Alk3 (Bmpr1a -Mouse Genome Informatics) in the developing AV canal (AVC) using cGATA6-Cre mice demonstrated that BMP signaling impacts AV impulse propagation by regulating the proper formation of the annulus fibrosus and the AVN (Gaussin et al, 2005;Stroud et al, 2007). Although these studies have provided valuable insights into the formation and function of the AVCS, many of the molecular details remain to be completely elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Accessory myocardial connections that can lead to preexcitation are commonly thought to result from malformation of the annulus fibrosus (6)(7)(8)(9). However, during development, the AV canal myocardium causes an adequate AV delay to allow synchronized alternating contraction of the atria and ventricles (10) in the absence of an annulus fibrosus.…”
Section: Introductionmentioning
confidence: 99%